Exploring African approaches to international law: Essays in honour of Kéba Mbaye - Viljoen, Frans (Pretoria University Law Press (PULP), 2022)
It is unfortunate that the idea that Africa contributes to international law, and has always done so, remains (in 2022) largely a side note, an auxiliary approach, rather than something widely accepted and deeply entrenched. It is cause for pause that this is also true in Africa itself. Exploring African approaches to international law: Essays in honour of Kéba Mbaye is a volume of essays that aims to contribute to a larger effort of imagining what possible approaches to international law Africa has adopted in the decades since the 1960s. It also recognises the legacy of the great Senegalese jurist Kéba Mbaye. Edited by Frans Viljoen, Humphrey Sipalla and Foluso Adegalu, the volume is divided into five broad thematic parts, and comprises eleven chapters. It covers the following themes: 'Kéba Mbaye in African approaches to international law', 'international legal theory', 'international human rights law', 'international environmental and criminal law' and 'teaching of international law'. This publication finds its origins in the 2017 Roundtable on African approaches to international law, held at the Centre for Human Rights, University of Pretoria. The explorations at the Roundtable on the concept of an 'African approach' to international law were taken further at the Kéba Mbaye Conference on African approaches to international law, held at the Senate Hall, University of Pretoria, in December 2018. This conference brought together around 80 students, academics, and members of civil society to address the many questions left unanswered by the death of Judge Mbaye, arguably Africa's greatest international law jurist of his generation. It provided a forum to continue discussions on 'African approaches to international (human rights) law', building on but rethinking and 'vernacularising' the Third World Approaches to International Law (TWAIL) approach. The contributions to this publication flow from papers presented at the conference. However, the reflections in the book extend beyond Kéba Mbaye as central figure. The result is a broad treatment of various aspects of African approaches to international law by thirteen authors (and co-authors), covering a wide range of generational, geographic and thematic backgrounds and perspectives.